Erratum—Vieira, L.M., Migotto, A.E. & Winston, J.E. (2010) Marcusadorea, a new genus of lepralioid bryozoan from warm waters. Zootaxa, 2348, 57–68. - Vieira, L. M.; Migotto, A. E.; Winston, J. E. (Zootaxa, 2010)
Page number 63, line 7: